Advancing Enhanced Weathering Modeling in Soils: Critical Comparison With Experimental Data - Matteo B. Bertagni; Salvatore Calabrese; Giuseppe Cipolla; Leonardo V. Noto; Amilcare Porporato (Journal of Advances in Modeling Earth Systems)
Abstract Enhanced weathering (EW) is a promising strategy to remove atmospheric CO2 by amending agricultural and forestry soils with ground silicate rocks. However, current model‐based EW assessments face large uncertainties stemming from the intricate interplay among soil processes, compounded by the absence of a detailed comparison with available observational data. Here, we address this critical gap by first advancing a dynamic, ecohydrological, and biogeochemical Soil Model for Enhanced Weathering (SMEW). We then conduct a hierarchical model‐experiment comparison with four experimental data sets of increasing complexity, from simple closed incubation systems to open mesocosm experiments. The comparison demonstrates SMEW's ability to capture the dynamics of primary variables, including soil moisture, alkalinity, and inorganic carbon. The comparison also reveals that weathering rates are consistently lower than traditionally assumed by up to two orders of magnitude. We finally discuss the implications for carbon removal scenarios and avenues for further theoretical and experimental explorations.